Strategi Pengembangan Pariwisata Desa Batununggul Kecamatan Nusa Penida Kabupaten Klungkung Bali - Destiny Alicia; Ida Ayu Suryasih (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
Batununggul Village is the administrative center of the Nusa Penida District. Almost all economic andtransportation activities are found in this village. Ease of accessibility, as the center of government, plus itstourist attraction, Nusa Penida has the potential to increase the number of tourist visits. Thus, theresearcher is interested in raising the topic of research on the tourism strategy of developing BatununggulVillage, Nusa Penida District, Klungkung Regency, Bali. The concept used as the basis in this research isstrategy, tourism development, tourism potential, tourist attraction, tourism industry. The method used is aqualitative research method with qualitative data analysis techniques and SWOT data analysis. The types ofdata used are qualitative and quantitative. Sources of data used are primary data and secondary data. Thedata was collected through observation, interviews, documentation. The technique of determininginformants in this research uses purposive sampling technique.The results of this study indicate that Batungul Village has tourism potential which is divided into 4components, i.e. attractions that can attract tourist visits. Amenities are all kinds of facilities andinfrastructure needed by tourists while in tourist destinations. Accessibility, namely transportation services,is an important access in tourism. Transportation makes it easy to move from one area to another.Additional services are things that must be provided by an agency/local government of a touristdestination, both for tourists and for tourism actors, amenities, accessibility and additional services. Basedon these components, it can be seen that the development strategy of Batununggul Village includes the SOstrategy, namely aggressively promoting through social media, the ST strategy, which is to provide a uniqueexperience that can make tourists stay longer in Batununggul village, the WO strategy, which is to provideguidance and training to village officials, local communities and teruna teruni to develop BatununggulVillage. WT's strategy is to develop marine tourism and utilize technology as a promotional medium.Keyword: Strategy, Development.